(untitled) (Applied Biological Research, 2024)
Transdermal patches offer a significant advantage for systemic Donepezil (DPZ) absorption by bypassing hepatic first-pass metabolism, which otherwise produces inactive Donepezil N-oxide and other hydroxylated metabolites. These patches enable the controlled and continuous release of medication into the bloodstream through intact skin over an extended period.This study aimed to develop and characterize DPZ transdermal patches using a central composite design. The patches were prepared with PVP K30, HPMC K15, and modified chitosan through the solvent-casting technique. The central composite design generated by Design Expert software was used to analyze the impact of independent variables on the response.FTIR analysis was conducted to examine DPZ-excipient interactions. The formulations of Donepezil transdermal patches (DTDP) demonstrated excellent physicochemical properties, including appearance, thickness, weight uniformity, folding endurance (FE), elongation at break, DPZ content, moisture content, and tensile strength. Among the formulations, DTDP-11 exhibited the highest DPZ release at 8, 16, and 24 hours.The patches were flexible, with a breakpoint at 161 folds. Tensile strength across all batches ranged between 0.422 and 0.433 mg cm⁻² h⁻¹, and the moisture content was within acceptable limits. In vitro testing confirmed consistent DPZ permeation across all patches, with DTDP-11 showing the best performance, indicating enhanced DPZ release.The study concluded that using HPMC K15 (125 mg), PVP K30 (40 mg), and modified chitosan (65.9 mg) effectively facilitated prolonged permeation and flexibility in DPZ transdermal patches.